Assessment of salivary matrix metalloproteinase (MMP8) and activated salivary matrix metalloproteinase (aMMP8) in periodontitis patients: a systematic review and meta-analysis - Boynes, Sean G.; Sofiyeva, Nigar; Saw, Tina; Nieto, Valerie; Palomo, Leena (Frontiers in Oral Health, 2025)
IntroductionPeriodontitis affects a significant portion of the global population and is associated with systemic health issues. Salivary biomarkers such as salivary matrix metalloproteinase-8 (MMP-8) and its activated form (aMMP-8) have been studied for their roles in tissue degradation and inflammation in periodontitis. This meta-analysis investigates the association between salivary MMP-8 and aMMP-8 levels and periodontitis.MethodsA systematic literature search was conducted utilizing PubMed, Embase, Web of Science, and Cochrane Library databases up to October 2023, yielding 35 studies that quantified MMP-8 or aMMP-8 in saliva from patients with periodontitis and healthy controls. Data were extracted, and standardized mean differences (SMD) with 95% confidence intervals (CI) were calculated. Heterogeneity was assessed, and subgroup analyses were performed based on saliva collection techniques. Meta-regression analysis evaluated the impact of publication year on heterogeneity.ResultsThe meta-analysis included 35 studies. Pooled results indicated significantly higher levels of MMP-8 and aMMP-8 in periodontitis cases compared to healthy controls (SMD: 2.71, 95% CI: 1.04–4.38, p = 0.002) with substantial heterogeneity (I2 = 94.5%). No significant difference was found between MMP-8 and aMMP-8 (p = 0.445). Subgroup analyses by saliva collection technique did not reduce heterogeneity significantly. Meta-regression showed that publication year did not impact heterogeneity. Small-study effects and publication bias were present, suggesting caution in interpreting the results.DiscussionThe findings support the potential of MMP-8 and aMMP-8 as biomarkers for periodontitis, although substantial heterogeneity and methodological differences among studies pose challenges. Standardized protocols and larger sample sizes are necessary to enhance the reliability of these biomarkers in clinical practice. Despite limitations, salivary diagnostics hold promise for non-invasive, early detection and monitoring of periodontitis.ConclusionSalivary MMP-8 and aMMP-8 levels are significantly associated with periodontitis, highlighting their potential as diagnostic biomarkers. However, methodological improvements and standardization are essential for their clinical application. Collaborative efforts and advancements in salivary diagnostics are crucial for improving periodontitis management and patient outcomes.